Ethnomedicinal Plants used against Gastrointestinal problem in Gingee Hills of Villupuram District, Tamil Nadu - R. Muralidharan and D. Narasimhan (Journal of Applied Pharmaceutical Science)
This study is a documentation of medicinal plants used for gastro intestinal problem by villagers around Gingee hills of Villupuram District. A total of 28 Dicot plants belong to 24 families are used to cure gastrointestinal problem. Isolation of active principles and anti-microbial activity should be studied on these medicinally plants. Emphasis also made for proper documentation and conservation of these medicinal plants.
Keywords: Community knowledge,Ethnobotany,Gingee hills,Gastro intestinal problems.